Penerapan Terapi Musik Klasikal Beethoven Pada Ibu Hamil Hipertensi Di Wilayah Puskesmas Bestari Kecamatan Medan Petisah Tahun 2024 - Vitalia Hanako Murni Simanjuntak; Zulkarnain Batubara; Rasmi Manullang; Lasria Yolivia Aruan (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Hypertension in pregnancy is a common pregnancy complication, affecting 2% of pregnant women worldwide. It is the cause of death of pregnant women in the world, hypertension is treated conventionally, namely hypertension-reducing drugs, but this conventional treatment has many problems because it is related to pregnant women which will definitely be related to the fetus they are carrying. At the Bestari Community Health Center, Medan Petisah District, the health status of mothers and children is good, but there are still problems for pregnant women who experience hypertension during their pregnancy, which is around 30%. The incidence of hypertension in pregnancy is high in the working area of the Bestari Community Health Center, Medan Petisah District, because people consume more than the amount of salt, the food menu is haphazard, and if they are treated with hypertension medication, they are not consumed because it will have a bad impact on their child, to solve the problem, to resolve the treatment. An alternative to non-pharmacological treatment is using music therapy and providing counseling about correct eating patterns. The aim of this community service is to increase knowledge and reduce the incidence of hypertension in pregnant women by using counseling methods and applying music therapy. Method: By providing counseling and music therapy, the results of the implementation of Beethoven's classical music therapy activities are: knowledge of the community (pregnant women) about eating patterns increased by approximately 89% and hypertension which was successful decreased in the 2-4th week of therapy, namely on average 110/70 mmHg..